Digital technology as a mechanism for the performance of institutions, with the Japanese company "AI Inside" and "Xiaomi" as case studies - Hezil, Soumia (The International tax journal, 2025)
This study addresses the theoretical framework of digital technology and its impact on institutional performance, emphasizing that digital transformation has become a strategic necessity in light of rapid technological development. It also reviews the components of digital technology, such as cloud computing and artificial intelligence, and how they contribute to improving operational efficiency, decision-making, and customer relations. The study also highlights the challenges institutions face in adopting these technologies and underscores the importance of strategic planning and the role of technology in enhancing innovation and competitiveness. The study concludes by analyzing case studies of successful companies like AI Inside and Xiaomi to illustrate how to achieve excellence and sustainable growth in the digital age.